A Comparative Analysis of Treatment Strategies for Concurrent ST-Elevation Myocardial Infarction and Infective Endocarditis: A Systematic Review - Reiny Laura Ningrum; Tirsa Wehelmina Ivonne Baguna (International Medical Journal Corp. Ltd, 2025)
Introduction : The concurrent presentation of ST-Elevation Myocardial Infarction (STEMI) and Infective Endocarditis (IE) represents a rare but highly lethal clinical challenge. Standard management protocols for atherothrombotic STEMI are often contraindicated or hazardous in the context of septic coronary embolism, the predominant pathophysiology in IE. This creates a significant therapeutic dilemma with no consensus guidelines to direct clinical decision-making. This systematic review aims to synthesize the available evidence on different treatment strategies—medical, percutaneous, and surgical—and their impact on mortality and major complications in this patient population. Methods : A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted from inception to the present day to identify all relevant studies, including case reports, case series, and observational cohort studies. The search included adult patients with a confirmed dual diagnosis of IE and STEMI. Data on study design, patient characteristics, treatment strategies, and a predefined list of at least 15 clinical outcomes were extracted. The primary outcome was in-hospital all-cause mortality. Due to the heterogeneity of the data and the predominance of case-level evidence, a narrative synthesis was performed. The methodological quality of included studies was assessed using the ROBINS-I tool for observational studies and a modified Joanna Briggs Institute checklist for case series and reports. Results : A total of 18 studies, comprising 91 patients, met the inclusion criteria. The included literature consisted of two observational cohort studies and 16 case reports or small case series. The primary mechanism of STEMI was septic coronary embolism in over 88% of cases (Roux et al., 2017). Three primary treatment strategies were identified: medical management alone, percutaneous coronary intervention (PCI), and definitive cardiac surgery. In-hospital mortality was exceedingly high in patients receiving medical management alone (85.7%, 6/7 patients). PCI-based strategies, particularly stenting, were associated with a significant risk of late complications, most notably mycotic aneurysm formation. An integrated surgical approach, combining valve replacement with coronary revascularization (e.g., coronary artery bypass grafting), was associated with the lowest reported mortality among interventional strategies in selected patient cohorts (10% in one registry's survival group) (Güvenç et al., 2021), although it is subject to significant selection bias. Major complications across all groups included cardiogenic shock, heart failure, and systemic embolic events, particularly ischemic stroke. Discussion : The evidence, though of low quality, suggests a significant divergence in outcomes based on treatment strategy, which is deeply intertwined with the underlying pathophysiology of septic embolism. The high mortality in the medically managed group likely reflects a cohort of patients too unstable for intervention. While PCI can restore acute coronary flow, the implantation of a stent into an infected artery poses a substantial risk of long-term septic complications. A definitive surgical approach that addresses both the valvular source of infection and the coronary occlusion appears to be the most effective strategy but is often precluded by hemodynamic instability or acute neurological injury. Conclusion : Concurrent STEMI and IE is a clinical catastrophe associated with high mortality. The optimal management strategy is highly individualized and necessitates an emergency multidisciplinary 'Endocarditis Heart Team' approach. The available evidence, while limited, supports early definitive surgery in hemodynamically stable patients without prohibitive neurological contraindications. PCI should be used judiciously, primarily as a bridging therapy, with a preference for techniques that minimize vessel trauma and avoid permanent implants. Prospective, multicenter registries are urgently needed to provide higher-quality evidence to guide the management of this devastating condition.